Effect of Digital Marketing Strategies on Consumer Buying Behaviour with reference to agriculture sector (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
Digital marketing in agriculture involves using digital platforms to promote and sell farm products. This includes multiple approaches like online marketing, search engine optimization, social media interaction, and email promotions. Through the use of online advertising, agricultural companies can extend their reach to a wider audience for their products. Reaching out to possible customers via digital platforms enables them to connect with people who truly care about their products. Additionally, online advertising offers creative ways for companies to connect with their clients. By implementing a strong digital marketing strategy, agricultural businesses can boost their sales and reach a wider audience than ever before. Consumer purchasing behaviour is significantly influenced by contemporary marketing techniques such as digital marketing, which incorporates tools like SEO, social media usage, and the development of e-commerce platforms to market agricultural products. Digital marketing allows consumers to personalize their buying journeys. Customers tend to prefer instant gratification rather than exploring new products. A brand's digital content can be tailored and modified to offer custom shopping experiences. This will significantly impact purchasing choices of consumers.